Successful treatment of extensive-stage small cell lung cancer with concurrent pleural and pericardial effusions: Case report - Kashima, Ayaka; Fukuda, Yosuke; Shimamura, Miri; Ijichi, Miharu; Sagara, Hironori (Frontiers in Oncology, 2022)
It is unclear whether pleural/pericardial drainage and pleurodesis/pericardiodesis should be performed before or after initiating chemotherapy in patients with chemotherapy-sensitive small-cell lung cancer. A 76-year-old woman presented to the emergency department with progressive dyspnea on exertion for a week. Chest computed tomography showed a mass shadow anterior to the left upper lobe, bilateral pleural effusions, and a circumferential pericardial effusion surrounding the heart. We diagnosed extensive-stage small-cell lung cancer based on the clinical course and pathological findings. We first performed pleurodesis and pericardial drainage and successfully initiated immune checkpoint inhibitor combined chemotherapy, with improved performance status. This case highlights the importance of aggressive drainage and pleurodesis/pericardiodesis, and suggests that drainage and pleurodesis/pericardiodesis should be considered before systemic chemotherapy in patients with concurrent pericardial or pleural effusions, even in patients with small-cell lung cancer that is sensitive to chemotherapy.